Dragons' teeth and thunderstones : the quest for the meaning of fossils - McNamara, Ken (Reaktion Books Ltd, 2020)
For at least half a million years, people have been doing some very strange things with fossils. Long before a few 17th-century minds started to decipher their true, organic nature, fossils had been eaten, dropped in goblets of wine, buried with the dead, adorned on bodies and even used to try and cause harm. What triggered such curious behaviour was the belief, passed down from prehistoric to Medieval times, that some fossils could cure illness, protect against being poisoned, ease the passage into the afterlife, ward off evil spirits and even kill those who were just plain annoying. But above all, to our early prehistoric ancestors living hundreds of thousands of years ago, fossils were the very stuff of artistic inspiration. Drawing on archaeology, mythology and folklore, Kenneth McNamara takes you on a journey through prehistory with these strange and curious stones, and explores humankind's unending quest for the meaning of fossils.